Interpersonal dynamics in chronic pain: The role of partner behaviors and interactions in chronic pain adjustment - Goubert, L.; Bernardes, S. F. (Current Opinion in Psychology, 2025)
Chronic pain affects one-third of adults globally, leading to significant disability and healthcare costs. This review highlights the role of interpersonal processes in chronic pain adjustment, focusing on how partner behaviors and interactions influence patient well-being and functioning. It synthesizes recent theoretical perspectives and empirical findings, discussing both potentially maladaptive responses, such as solicitousness and invalidation, and adaptive behaviors, including validation of emotional disclosures and encouragement of valued activities. The review identifies gaps in current research, emphasizing the need for clearer conceptualizations of partner behaviors, advanced methodological approaches to capture dynamic interactions, and robust measurement tools. Prioritizing couple interventions that enhance communication, relational dynamics, and partner support for functional autonomy may lead to more holistic and effective chronic pain management.